Clinical utility of small bowel ultrasound assessment of Crohn's disease in adults: a systematic scoping review. Issue 4 (23rd June 2021) - Radford, Shellie Jean; Clarke, Chris; Shinkins, Bethany; Leighton, Paul; Taylor, Stuart; Moran, Gordon
Abstract : Background: Ultrasound (US) is an alternative to magnetic resonance enterography, and has the potential to significantly reduce waiting times, expedite clinical decision-making and improve patient experience. Point of care US is an advantage of the US imaging modality, where same day scanning, interpretation and treatment decisions can be made. Aim: To systematically scope the literature on point of care US use in small bowel Crohn's disease, generating a comprehensive list of factors relating to the current understanding of clinical utility of this imaging modality. Methods: Searches included MEDLINE, EMBASE, Cochrane Library, Cumulative Index to Nursing and Allied Health Literature, PsycINFO, clinicaltrial.gov, 'TRIP' and Epistemonikos. Reference lists of included studies were hand searched. Search terms were searched for as both keywords and subject headings (MeSH) as appropriate. Searches were performed with the 'suggested search terms' and 'explode' selection, and restricted to 'human', 'adult' and 'English language' publications. No date limits were applied to be as inclusive as possible. Two investigators conducted abstract and full-text review. No formal quality appraisal process was undertaken; however, quality of sources was considered when reporting findings. A narrative synthesis was conducted. Results: The review included 42 sources from the UK, Europe, Japan, Canada and the USA. Small bowel ultrasound (SBUS) has been shown to be as accurate in detecting the presence of small bowel Crohn's disease, is quicker, safer and more acceptable to patients, compared with magnetic resonance enterography. SBUS is used widely in central Europe and Canada but has not been embraced in the UK. Further research considering economic evaluation, clinical decision-making and exploration of perceived barriers to future implementation of SBUSs is required.